Perceptions of nicotine in current and former users of tobacco and tobacco harm reduction products from seven countries. Issue 3 (10th July 2020) - Rajkumar, Sarah; Adibah, Nada; Paskow, Michael Jonathan; Erkkila, Brian Eric
Abstract : Purpose: Nicotine is widely known as a tobacco constituent and for its use as a tobacco cessation aid. The development of new devices for nicotine delivery in recent years has led to uncertainty among consumers regarding the health risks of nicotine relative to tobacco. The purpose of this study was to discover if current and former consumers of tobacco and tobacco harm reduction (THR) products could distinguish between "nicotine" and "cigarettes" and examined the preceding media dialogue to determine if conflicting messages by the media influence public perceptions. Design/methodology/approach: A quantitative survey was administered online in Norway (NO), Japan (JP), the United Kingdom (UK) and the United States (US), while face-to-face computer-aided interviews were conducted with randomly selected samples in India (IN), Greece (GR) and South Africa (SA). Participants were between 18 and 69 years of age and either current users of tobacco and THR products or previous users who quit within the past five years. Questions assessed beliefs about harmfulness of nicotine. Nicotine and other products and substances were also independently rated for harmfulness on a scale of 1–10 and subsequently compared. In addition, the authors examined the media dialogue of top media outlets in four countries to assess the potential influence on people's beliefs. Findings: A total of 54, 267 participants (NO: 1, 700, JP: 2, 227, UK: 2, 250, USA: 2, 309, IN: 41, 633, GR: 1, 801, SA: 2, 359) were sampled with the percentage of women participants ranging from 14.8% (IN) to 53.8% (UK). Between 68.3% (men, IN) and 88.7% (men, USA) of current consumers believed nicotine is harmful. Current consumers who agreed with the statement that nicotine is the primary cause of tobacco-related cancer ranged from 43.7% (men, UK) to 78.0% (men, SA). In six countries nicotine was rated nearly as harmful as cigarettes and alcohol, while other substances such as sugar, salt or caffeine, were usually rated as less harmful. Research limitations/implications: A large proportion of consumers across all surveyed countries view nicotine and cigarettes similarly. Clearer communication on the harmful properties of both by the media is needed to help consumers make informed decisions about products across the continuum of risk. Messaging to consumers, especially via the media, propagates misinformation about the relative harms of tobacco and nicotine through reporting that is often incomplete and biased toward more negative aspects. Originality/value: This study specifically assessed public perceptions of nicotine as opposed to products containing nicotine, which is the focus of previous studies. Apart from showing that consumers often incorrectly perceive nicotine and cigarettes as similar in terms of harmfulness, the authors highlight the need for more accurate and complete reporting by the media to clarify widespread misunderstandings and mitigate public uncertainty.